Long-term trends in water level fluctuations in lowland lakes in central Europe (Northern Poland) - Mariusz Ptak; Katarzyna Szyga-Pluta; Mariusz Sojka (Scientific Reports)
Abstract Water level fluctuations in lakes are one of the key parameters affecting their functioning and other environmental elements present in their vicinity. They also provide information about the entirety of processes occurring in the catchment area, both natural and anthropogenic, the result of which is the filling of the lake basin with water. This study analyses changes in water levels of 25 lakes in Poland based on maximum, average, and minimum annual values from the period 1963–2022. From the point of view of water circulation, the obtained results can generally be considered favourable. In most cases, a statistically significant increase in the lowest (on average 4.6 cm per decade) and average (on average 3.5 cm per decade) levels was noted, ensuring the stabilisation of water conditions. On the other hand, there is a levelling of the highest levels (only five lakes showed an increasing trend, on average by 5.2 cm per decade) and amplitude of fluctuations. In the spatial arrangement, no clear patterns were recognised in the regional distribution of individual characteristics, and the factors determining water level fluctuations have a local character. The role of hydraulic infrastructure is significant, where water level regulation is subordinated to economic objectives. In the context of increasingly observed water deficits, it is necessary to monitor the further course of water levels and flexibly adopt the issues of their regulation.